Tetracycline Antibiotic Removal from Water by Wood Filters with Well-Arranged Natural Porous Structure - Zhu, Yaqin (Langmuir : the ACS journal of surfaces and colloids, 2025)
Antibiotic pollution is a crucial global environmental issue, and it is necessary to develop simple, economical, and effective filtration materials for the removal of antibiotics from water. Wood, a plentiful and ecofriendly natural material characterized by a hierarchical porous architecture, robust mechanical strength, and abundant functional groups, has been adopted as an adsorptive filter for water purification. However, the mechanism of natural wood filters for removing pollutants from water has not been analyzed. In this study, we prepared three wood filters (balsawood, basswood, and Chinese fir) with different pore structures for the removal of the tetracycline (TC) antibiotic. We systematically investigated the structures and properties of the three wood filters to establish clear structure-property-performance relationships. By comprehensively considering the flux and TC removal efficiency, we selected the basswood filter as the optimal filter and further discussed the removal efficiency of the basswood filter and its removal mechanism for TC. When using five basswood filters, after continuously treating 120 mL of 0.5 mg L-1 TC solution at 5000 L m-2 h-1, a relatively high removal efficiency of over 85% could still be achieved. The filters retained ∼80.5% of their removal efficiency after five regeneration cycles, demonstrating excellent reusability. The further studies prove that there are three primary interaction forms in the process of TC removal by the basswood filter, which are electrostatic interaction, hydrogen bonding interaction, and π-π interaction. This is expected to be widely applied in actual wastewater treatment